Pengobatan otitis eksterna yang disebabkan oleh Malassezia spp. pada anjing lokal: pendekatan antijamur non-sistemik - Rasmana, I Komang Juanda; Aryana, Carrisa Saraswati Putri; Perayadhista, Ni Made Devityasih; Widyasanti, Ni Wayan Helpina; Putra, I Putu Cahyadi (ARSHI Veterinary Letters, 2025)
Malassezia spp. are part of the commensal microbiota on the skin and ears of dogs; however, under certain conditions, they can overgrow, triggering otitis externa. Systemic therapy is effective; however, its use is limited by its potential for resistance and hepatotoxic effects. This article reports a case of dextra otitis externa caused by Malassezia spp. in a 1.5-year-old male dog. On initial examination, the dog showed swelling of the right ear flap, scratching wounds, yellowish exudate, narrowing of the ear canal, as well as alopecia, erythema, and nodules on the ear flap and neck. The diagnosis was confirmed by clinical examination and cytology, which revealed the presence of Malassezia spp. The treatment consisted of ear cleaning with a 3% chlorhexidine solution (topical, q12h for 14 days), bathing with a 2% miconazole nitrate-medicated shampoo, and additional therapy with antibiotics, prednisone, chlorpheniramine maleate, and supplements. Evaluation at the 7-day post-treatment follow-up showed a marked clinical improvement. At the 25-day post-treatment follow-up, the patient recovered without recurrence. This case report confirms that topical antifungal therapy with supportive therapy is effective for the treatment of Malassezia spp. in dogs.